Dual career policy at federal universities in Brazil: analysis of academic and sporting support - Silva, Junior Vagner Pereira da (Frontiers in Sports and Active Living, 2024)
Internationally, the implementation of holistic programs aimed at academic, financial and retirement preparation support for student-athletes who find themselves in dual careers, such as university students, has been widespread and intensified. However, little is known about the subject in the Brazilian national context, because although there are related studies, they are punctual and related to specific universities. In view of the above, this study aimed to investigate public policy aimed at student-athletes at Brazilian federal universities. This is an exploratory, qualitative, cross-sectional and documentary study, using the websites, internal regulations and public notices of 69 Brazilian federal universities for the year 2023, using the content analysis technique. The results indicate that 72.05% offer some kind of support to DC based on the holistic model, 66.17% of which is academic and 60.29% sports. Among the academic support, the flexibility of assessments (57.35%) and the differentiated treatment of absences (51.47%) were close. The sporting support is centered on partial payment of competition costs (60.29%) and athlete grants are restricted to 20.58% of universities. It can be concluded that Brazil's federal universities have dual career policies that include support from holistic model (academic), but with incipient scholarship coverage (sporting).